RecBCD enzyme is altered upon cutting DNA at a chi recombination hotspot. - Taylor, A F (1992)
During its unidirectional unwinding of DNA, RecBCD enzyme cuts one DNA strand near a properly oriented Chi site, a hotspot of homologous genetic recombination in Escherichia coli. We report here that individual DNA molecules containing two properly oriented Chi sites were cut with about 40% efficiency at one or the other Chi site but not detectably at both Chi sites. Furthermore, initial incubation of RecBCD with Chi-containing DNA reduced its ability both to unwind DNA and to cut at Chi sites on subsequently added DNA molecules much more than did initial incubation with Chi-free DNA; the nuclease activity was less severely affected. These results imply that RecBCD loses its Chi-cutting activity upon cutting at a single Chi site and provide a mechanism for ensuring single genetic exchanges near the ends of DNA molecules.